The role in thanatogenesis of generalized brain edema in ischemic cerebral infarction (computer-morphometric research) - E. A. Dyadyk (Patologìâ)
This work presents the results of computer-morphometric study of perivascular and pericellular free (oedematous) spaces in brain cortex at death from the ischemic cerebral infarction and from reasons unconnected directly with cerebral pathology. It was revealed, that the mean area of perivascular spaces (vasogenic edema index) at brain infarction in 13 times exceeds such at extracerebral pathology, and mean area of pericellular spaces (cytotoxic edema index) – almost in 12 times, but also it substantially differs on the degree of variation (in 2,5 times higher, than area of perivascular spaces).